Multiple microRNA signature panel as promising potential for diagnosis and prognosis of head and neck cancer - Subha, Sethu Thakachy; Jun, Wei Chin; Yoke, Kqueen Cheah; Mohtarrudin, Norhafizah; Saidi, Hasni Idayu (Springer, 2021)
MicroRNAs are small non-coding RNA that regulate gene expressions of human body. To date, numerous studies have reported that microRNAs possess great diagnostic and prognostic power in head and neck cancer and had governed a lot of attention. The factor for the successfulness of miRNAs in these aspects is due to cancer being fundamentally tied to genetic changes, which are regulated by these miRNAs. Head and neck cancer, leading the world record for cancer as number sixth, is caused by multiple risk factors such as tobacco consumption, alcohol consumption, dietary factors, ethnicity, family history, and human papilloma virus. It derives at locations such as oral cavity, pharynx, larynx, paranasal sinus and salivary gland and have high rate of mortality with high recurrence rate. Besides, head and neck cancer is also usually having poor prognosis due to its asymptomatic nature. However, this diagnostic and prognostic power can be further improved by using multiple panels of miRNA as a signature or even combined with TNM staging system to obtain even more remarkable results. This is due to multiple factors such as tumour heterogeneity and components of the tumour which may affect the composition of miRNAs. This review covers the examples of such miRNA signatures, compare their diagnostic and prognostic powers, discuss some controversial roles of unreported miRNAs, and the molecular mechanisms of the miRNAs in gene targeting and pathways.